1976
DOI: 10.1097/00132586-197602000-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Route of Administration on the Clinical Action of Diazepam

Abstract: It is generally agreed that absorption of drugs occurs more rapidly following their intramuscular injection than when given by mouth.'-3 This is the basis for the giving of premedicants by injection, which although challenged by Inglis & Barrow in 1965,4 is still widely practised.Recently, in a pilot study, McCaughey & Dundee' found better sedation when 10 mg diazepam was given by mouth than following its intramuscular injection, but their investigation was carried out on a small number of patients. In view of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
2

Year Published

1976
1976
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
2
10
2
Order By: Relevance
“…12 The infrequent mild discomfort at the IM injection site was notable, particularly because early reports describe unacceptable pain upon IM injection of diazepam in the thigh. 23,24 Such pain was not observed in the present studies. Of the 92 injections administered in both studies, 9 (10%) injections were associated with generally mild injection site pain.…”
Section: Discussioncontrasting
confidence: 77%
See 1 more Smart Citation
“…12 The infrequent mild discomfort at the IM injection site was notable, particularly because early reports describe unacceptable pain upon IM injection of diazepam in the thigh. 23,24 Such pain was not observed in the present studies. Of the 92 injections administered in both studies, 9 (10%) injections were associated with generally mild injection site pain.…”
Section: Discussioncontrasting
confidence: 77%
“…The infrequent mild discomfort at the IM injection site was notable, particularly because early reports describe unacceptable pain upon IM injection of diazepam in the thigh 23,24 . Such pain was not observed in the present studies.…”
Section: Discussioncontrasting
confidence: 53%
“…However, MCCAUGHEY & DUNDEE (1972) reported that better and more rapid sedative effects are achieved after oral than after intramuscular administration. Since facilities for estimating drugs in plasma or serum have improved it has been demonstrated that definitely higher plasma and serum levels of diazepam are achieved when the drug is administered by mouth than when the same amount of diazepam is injected intramuscularly into the buttock, thigh or shoulder (KANTO 1974;ASSAF et al 1975;KORTTILA & LINNOILA 1975a). Furthermore, pain frequently occurs after an intramuscular injection of diazepam (ASSAF et al 1975;KORTTILA & LINNOILA 1975b).…”
Section: I05mentioning
confidence: 99%
“…The various factors responsible for variability among the population are genetic polymorphism Hruby and Anzenbacher, 1997;Board et al, 1998;Ozawa, 1998;Neber and Roe, 2001;Lamba et al, 2002;Miners et al, 2002;Nagar and Remmel, 2006;Hildebrandt et al, 2007), age (Wilkinson, 1997;Benedetti et al, 2007), gender (Shapiro et al, 1995;Gutmann et al, 2005), species (Hruby and Anzenbacher, 1997), strain (Chen et al, 2005;Wang et al, 2006;Joseph et al, 2007), diet and environmental factors (Wilkinson, 1997;Nowell et al, 1999;Huang and Lesko, 2004;Felton and Malfatti, 2006), induction and inhibition of drug-metabolizing enzymes Lin and Lu, 1998;Lu, 1998;Handschin and Meyer, 2003;Xu et al, 2005), and induction and inhibition of drug influx and efflux transporters (Suzuki and Sugiyama, 2000;Kim, 2002;Lau et al, 2004;Endres et al, 2006;Lin, 2007). Also, physiological conditions such as pregnancy (Larrey et al, 1986;Tsutsumi et al, 2001), pathological conditions or disease states (Wilkinson, 1997), route of administration (Assaf et al, 1975;Shand et al, 1975;Houston and Levy, 1976), dosing strength, and the dosage form can also impact drug-drug interactions. Induction and inhibition of the drug-metabolizing enzymes and efflux transporters by ligand-based NR activation are discus...…”
Section: Factors Affecting the Drug Metabolismmentioning
confidence: 99%